Radical cyclization/ipso-1,4-aryl migration cascade: Asymmetric synthesis of 3,3-difluoro-2-propanoylbicyclo[3.3.0]octanes - Watcharaporn Thaharn (2018)
A novel method for the asymmetric synthesis of 3,3-difluoro-2- propanoylbicyclo-[3.3.0]octanes involves an unprecedented intramolecular radical cyclization/ipso-1,4-aryl migration cascade. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.